Adipose-Derived Stem Cells Alleviate Radiation-Induced Muscular Fibrosis by Suppressing the Expression of TGF-β1. (16th November 2015) - Sun, Wei; Ni, Xinchu; Sun, Suping; Cai, Leiming; Yu, Jingping; Wang, Jian; Nie, Bin; Sun, Zhiqiang; Ni, Xinye; Cao, Xiufeng
Abstract : We aim to investigate the effects of adipose-derived stem cells (ASCs) transplantation on irradiation-induced skeletal muscle fibrosis. Sixty-four rabbits were randomly divided into ASCs group and PBS group followed by irradiation at unilateral hip with a single dose of 80 Gy. Nonirradiated side with normal skeletal muscle served as normal control. Skeletal muscle tissues were collected from eight rabbits in each group at 1 w, 4 w, 8 w, and 26 w after irradiation. Migration of ASCs was observed in the peripheral tissues along the needle passage in the injured muscle. The proportion of the area of collagen fibers to the total area in sections of ASCs group was lower than those of PBS groups at 4 w, 8 w, and 26 w after irradiation. Significant decrease was noted in the integrated optimal density of the transforming growth factorβ 1 (TGF-β 1) in the ASCs group compared with those of PBS group at 4 w, 8 w, and 26 w after irradiation. Moreover, the expression of TGF-β 1 was lower in the ASCs group compared to those of the PBS group at each time point determined by Western blot analysis. ASCs transplantation could alleviate irradiation fibrosis by suppressing the level of TGF-β 1 in the irradiated skeletal muscle.